Implementation of a Teledentistry Platform for Dental Emergencies for the Elderly in the Context of the COVID-19 Pandemic in Chile. (22nd March 2022) - Beltrán, Víctor; von Marttens, Alfredo; Acuña-Mardones, Pablo; Sanzana-Luengo, Cristina; Rueda-Velásquez, Sandra J.; Alvarado, Eloy; Flores, Marco; Cerda, Angeline; Venegas, Bernardo
Abstract : Objectives . To develop and implement a "semi-presential" technology platform to support urgent and priority dental care for the elderly in the context of the COVID-19 pandemic among the Chilean population. Methods . A dental mobile clinic was implemented along with the development of a technological platform designed to support emergency and priority dental procedures, including teleconsultation with specialists. Under strict biosafety protocols, dental care was provided in five Chilean regions between February and May 2021. Sociodemographic, medical, and dental data were recorded. Results . A total of 135 patients over sixty years old, with a mean age of 72 years, were treated, 48 males and 87 females were attended between February and May 2021 in five different regions of Chile. 53.3% required immediate or urgent treatment, and 24.4% were derived to specialists from whom 60.6% needed immediate or urgent treatment. 74.3% of teleconsultations were derived to an oral pathology specialist. Conclusion . It was shown that a "semi-presential" technology platform implemented in a mobile dental clinic can help elderly people who are impeded to look for traditional dental assistance during a pandemic.